Sex-related differences in geometry, plaques and shear stress related plaque-progression in human coronary arteries. (25th November 2020) - Wentzel, J.J; Papafaklis, M; Antoniadis, A; Takahashi, S; Cefalo, N.V; Cormier, M; Saito, S; Coskun, A; Stone, P.H
Abstract: Background: Atherosclerosis manifests itself differently in women compared to men. Since the pathophysiology of atherosclerotic plaques is known to be related to endothelial shear stress (ESS), it was hypothesized that female compared to male coronary arteries demonstrate a different i) ESS and ii) ESS related plaque progression. Methods: 1183 coronary arteries (male/female:944/239) from the PREDICTION trial were studied for differences in vessel geometry (plaque area (PA) and lumen area (LA)), hemodynamic parameters (flow, minimal ESS over 90 degree arc (minESS) and maximal ESS over 90 degree arc (maxESS)) and ESS related plaque progression (1 year follow up) measured as change in maximal plaque thickness and plaque burden comparing female to male arteries. Arterial geometry and ESS measures were derived from IVUS-based vascular profiling and reported per 3 mm segments. For plaque progression studies minESS was subdivided into low, mid and high (<1, 1–1.7, >1.7 Pa). To test statistical differences univariate anova or linear mixed models were used. Results: 13030 3mm-segments (m/f: 10.465/2565) were analyzed. Female compared to male coronary arteries were smaller and presented with less plaque area (Table I). No differences in average ESS, minESS and maxESS were found for male versus female coronary arteries, partly explained by the lower flows in female arteries (Table I). The ESS-related plaque growth showed for both sexes an significant inverse relationship between maximal wall thickness (Figure, left) and plaque burden (Figure, right) and the three minESS categories. However, ESS-related plaque growth was not different for male vs females. Conclusion: Our data demonstrated that vessel and plaque size are smaller in female compared to male coronary arteries. However, ESS and ESS related plaque progression were not different. Funding Acknowledgement: Type of funding source: None